(untitled) (Acta Polytechnica CTU Proceedings, 2021)
This paper aims to summarize possibilities how to create data models of high-speed railway turnouts. The turnouts designed for high-speed operation require specific geometric solution. As the UIC RailTopoModel is considered an international recommendation in the field of data modeling of railway infrastructure, this issue is assessed in terms of models based on its principles. Solving this problem can affect the future development of the Multipurpose Railway Infrastructure Model gradually emerging at the CTU Railway Laboratory in Prague using the RailTopoModel principles. Whereas the RailTopoModel itself does not define any specific types of entities, the railML® 3.1 specifications are also used for assessment purposes. Turnouts are viewed both in terms of topology and in terms of functional infrastructure. In the final sections, recommendations are given on how to deal with the problems found, e. g. in terms of implementation into the Multipurpose Railway Infrastructure Model.